2012
DOI: 10.4315/0362-028x.12-101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Antibiotic-Resistant Salmonella Isolates from Retail Meat from Markets in Northern Vietnam

Abstract: A total of 118 Salmonella isolates were detected from 283 retail meat samples (135 pork and 148 chicken meat) purchased at retail markets in Northern Vietnam. Thirteen serovars, including Infantis, Anatum, Rissen, Reading, Emek, Typhimurium, Blockley, London, Newport, Derby, Weltevreden, Albany, and Hadar, were determined. Resistance to tetracycline (54.2%), sulfonamides (52.5%), streptomycin (41.5%), trimethoprim (36.4%), chloramphenicol (35.6%), and ampicillin (33.1%) was commonly seen in the Salmonella iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
2
15
2
Order By: Relevance
“…The prevalence of Salmonella in beef samples in our research study is higher as compared to previous research studies [33][34][35][36]. However, some research studies have reported more than 60% prevalence in beef samples [37][38][39][40]. The Salmonella prevalence in beef is much lower in developed countries like USA due to strict control measures.…”
Section: Discussioncontrasting
confidence: 70%
“…The prevalence of Salmonella in beef samples in our research study is higher as compared to previous research studies [33][34][35][36]. However, some research studies have reported more than 60% prevalence in beef samples [37][38][39][40]. The Salmonella prevalence in beef is much lower in developed countries like USA due to strict control measures.…”
Section: Discussioncontrasting
confidence: 70%
“…With the exception of tetracyclines, against which most (77·8%) isolates were resistant, levels of resistance against ampicillin, chloramphenicol, and nalidixic acid were generally lower (22·8–27·0%) compared to NTS isolates from meat samples in northern Vietnam (24·5–39·8%) [ 12 , 41 ]. We found a strong association between group B serovars and AMR, independent of the animal host species, with the highest prevalence of MDR corresponding to mST, followed by ‘other’ group B serovars.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ST10 E . coli isolates have been frequently identified in humans and food products associated with a diversity of ESBL genes, including TEM-52 [ 15 , 19 , 50 ]. In addition, isolates belonging to CC23 ( bla CTX-M-15 ) and CC38 ( bla CTX-M-9 group ) were found in this study.…”
Section: Discussionmentioning
confidence: 99%